The impact of maintainability on the manufacturing system architecture. Issue 15 (3rd August 2017) - Gu, Xi
Abstract : The rapid development of big data technologies can improve the maintainability of machines and equipment in manufacturing systems, which could impact the selection of the optimal system architecture. In this paper, two typical architectures for large manufacturing systems − serial lines in parallel and reconfigurable manufacturing systems − are considered, and their productivities are compared. A decision locus is calculated that divides the configuration space into two areas; in each area, one of the architectures is the preferred one. It is also investigated how the locus is affected by different parameters, such as system size, buffer capacity and machine or gantry maintainability. The analysis provides valuable managerial insights for designing the architecture of large manufacturing systems.